SARS-CoV-2 Among Migrants Recently Arrived in Europe From Low- and Middle-Income Countries: Containment Strategies and Special Features of Management in Reception Centers - Silvia Fabris; Silvia Fabris; Gabriella d'Ettorre; Gabriella d'Ettorre; Ornella Spagnolello; Alessandro Russo; Maurizio Lopalco; Fausto D'Agostino; Fausto D'Agostino; Paolo Vassalini; Paolo Vassalini; Luigi Celani; et al. (Frontiers Media S.A., 2021)
Despite the "migrants and COVID-19" topic has been neglected since felt marginal concerning other aspects of the SARS-CoV-2 pandemic, it represents a relevant public health issue in the European countries. This report describes COVID-19 containment strategies adopted in a large Italian reception center hosting recently arrived asylum-seeker migrants. Risk assessment and prevention measures adopted were described. Geo-spatial epidemiological analysis of the outbreak was reported. Significant gaps in the knowledge of self-protection measures from contagious diseases and in the perception of the pandemic risk were observed in migrants; health promotion activities, targeted to remove cultural barriers and improve behaviors appropriate to individual protection, were able to fulfill this gap. In low-resource settings, especially in closed communities, the implementation of social distancing strategies, the systematic use of individual protection devices, and active syndromic surveillance are essential tools to limit the risk of outbreaks. In the event of an outbreak, it is relevant to rapidly activate containment procedures based on systematic screening, isolation, and quarantine, taking into consideration the limits of tracing contacts within a closed community. Not being able to trace certain contacts, the geo-spatial epidemiological analysis of cases distribution could be key in the management of the outbreak. Interestingly, positive cases identified in our facility were all clinically pauci-symptomatic or asymptomatic. Dedicated strategies are needed to minimize the chance of SARS-CoV-2 transmission in a limited space such as reception centers and a vulnerable population such as migrants.